Rethinking poverty : income, assets, and the Catholic social justice tradition - Bailey, James P. (James Patrick), 1960- (Catholic social tradition series., 2010)
In this work the author argues that most contemporary policies aimed at reducing poverty in the United States are flawed because they focus solely on insufficient income. He contends that traditional policies such as minimum wage laws, food stamps, housing subsidies, earned income tax credits, and other forms of cash and non cash income supports need to be complemented by efforts that enable the poor to save and accumulate assets. Drawing on Michael Sherraden's work on asset building and scholarship by Melvin Oliver, Thomas Shapiro, and Dalton Conley on asset discrimination, the author presents us with a novel and promising way forward to combat persistent and morally unacceptable poverty in the United States and around the world. This book makes use of a significant body of Catholic social teachings in its argument for an asset development strategy to reduce poverty. These Catholic teachings include, among others, principles of human dignity, the social nature of the person, the common good, and the preferential option for the poor. These principles and the related social analyses have not yet been brought to bear on the idea of asset building for the poor by those working within the Catholic social justice tradition. This book redresses this shortcoming, and further, claims that a Catholic moral argument for asset building for the poor can be complemented and enriched by Martha Nussbaum's "capabilities approach." This book will affect current debates and practical ways to reduce poverty, as well as the future direction of Catholic social teaching.